Quantitative evaluation of urban appearance and public environmental sanitation policies in China: based on LDA-PMC model - Hu, Yandi; Xu, Yingda (Frontiers in Environmental Science, 2025)
BackgroundWith the rapid acceleration of urbanization in China, issues related to urban appearance and public environmental sanitation have become increasingly prominent, and the effectiveness and scientific rigor of relevant policies have attracted widespread attention. Given that China’s governance experience serves as a key reference for developing countries, the quantitative evaluation of these policies holds significant theoretical and practical significance.MethodsThis study aims to conduct a comprehensive analysis, spanning from semantic mining of policy texts in the quantitative assessment, by integrating the Latent Dirichlet Allocation (LDA) and Policy Modeling Consistency (PMC) methods. This approach provides a scientific tool for optimizing urban appearance and public environmental sanitation policies. First, the LDA model was applied to extract themes from policy texts of 159 cities, identifying five core themes: public management tools, governance of citizens’ behaviors, supporting measures, participating subjects, and policy targets. Subsequently, a PMC evaluation system, comprising 9 primary variables and 31 secondary variables, was developed to assign quantitative scores and conduct a visual analysis of policies in 9 representative provinces.ResultsThe results showed that policy quality exhibited a “ladder-like disparity aligned with regional economic levels”: policies in international metropolises and economically vibrant regions mainly were of high quality (with scores ranging from 5.5 to 7.5), while those in less developed areas were generally of low quality (with all scores below 4.5), with a correlation coefficient of 0.82 (p<0.01) between policy quality and regional economic level. Meanwhile, the policy structure was characterized by four imbalances: prioritizing institutional frameworks over implementation details, hardware construction over ideological guidance, long-term planning over short-to-medium-term alignment, and administrative management over public participation.ConclusionThe study indicates that the quality of urban appearance and environmental sanitation policies is significantly correlated with regional economic development, but constrained by structural imbalances. The integrated LDA-PMC approach can effectively support the full-chain analysis of policy texts. In the future, efforts should focus on enhancing inter-regional policy coordination, improving implementation safeguards, refining public participation mechanisms, and establishing a dynamic policy revision system to adapt to the development needs of new-type urbanization.